The Influence of Financial Literacy and Demographic Factors on Investment Decisions in the Capital Market - Yeti Asrini; Agus Zul Bay; Niar Astaginy (Politeknik Baubau, 2026)
The growing number of capital market investors in Southeast Sulawesi demonstrates popular interest in investment as a long-term financial management strategy. However, this condition contrasts with the current disparity in financial literacy levels and the influence of demographic factors, which may impair individuals' capacity to make prudent investment decisions. The goal of this research is to study how knowledge of finances and demographic elements influence investment decisions of stock investors in Southeast Sulawesi. The context of this research is the paradox between the actual rapid increase in capital market investors along with the low degree of national monetary literacy, which is causes hesitation and the possibility of poor investment decisions. This study employs a survey as a quantitative method. Purposive sampling consists of 110 selected stock investors. Primary surveys were used to gather data, which was then examined utilising the SPSS 30.0 program. The outcomes showed that investment decisions are significantly and positively impacted by financial knowledge (β = 0.449; t = 4.283; p < 0.05). characteristics of the population also have a favourable and noteworthy impact on investing choices (β=0.291; t=2.780; p<0.005). Both independent variables can be responsible for 47.2% of the variance in the choice to invest variables simultaneously. This research found that knowledge of finance and demographic attributes are the main factors that influence capital market investment choices. The autocomes show the actual importance of organized financial education.